Wild edible plant Diversity of Kotagiri Hills - a Part of Nilgiri Biosphere Reserve, Southern India - A, Rajendran; R, Sasi; M, Maharajan (Journal of Research in Biology, 2011)
The present study documented indigenous knowledge on wild edible plant resources from the tribe Irulas of Kotagiri at Nilgiri Hills. They are partially or fully dependent on the wildresources for their nutritional requirements. A total of 50 - plants were identified belonging to 31- families under 43 - genera. The present study observed that the tribal communities of the study area fulfill their food deficiency by supplementing wild food plants in their daily diet